2013
DOI: 10.4269/ajtmh.13-0108
|View full text |Cite
|
Sign up to set email alerts
|

Factoring Quality Laboratory Diagnosis into the Malaria Control Agenda for Sub-Saharan Africa

Abstract: Abstract. Recent progress in malaria control in sub-Saharan Africa has been achieved primarily through provision of insecticide-treated nets, indoor residual spraying, and antimalarial drugs. Although these interventions are important, proper case identification and accurate measurement of their impact depend on quality diagnostic testing. Current availability of diagnostic testing for malaria in sub-Saharan Africa is inadequate to support disease management, prevention programs, and surveillance needs. Challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The observations from the QA pilot are consistent with findings from another recent external QA programme implemented in a limited number of rural health facilities in western Kenya and provide additional evidence for a coordinated approach to strengthening malaria diagnostics across the larger clinical and laboratory systems [21, 24]. Significant gains were observed in malaria diagnostic QA/QC practices over the pilot.…”
Section: Discussionsupporting
confidence: 79%
“…The observations from the QA pilot are consistent with findings from another recent external QA programme implemented in a limited number of rural health facilities in western Kenya and provide additional evidence for a coordinated approach to strengthening malaria diagnostics across the larger clinical and laboratory systems [21, 24]. Significant gains were observed in malaria diagnostic QA/QC practices over the pilot.…”
Section: Discussionsupporting
confidence: 79%
“…The findings above are supported by (Aidoo,2013) who found that malaria case management requires coordinated efforts by several healthcare professionals for laboratory tests to have a significant impact on malaria control and elimination, a paradigm shift is needed in patients care (Aidoo, 2013). Also, prompt and accurate diagnosis of malaria is the key to effective disease management, guiding the management of febrile patients and reducing the unnecessary use of anti-malarial drugs.…”
Section: Private Laboratory Techniciansmentioning
confidence: 78%
“…7 A coordinated approach in offering pre-service clinical and laboratory training together with systems that support scale-up of laboratory services could provide the means not only for effective malaria case management but also for management of non-malaria febrile illnesses, disease surveillance and accurate control programme evaluations. 8 Another study from Namibia showed that the distribution of RDT in 2005 led to more accurate diagnosis, which explained the sharp decline in malaria cases beginning in 2006. 9 The study indicated, however, that personnel training and supervision in the use of these tests remained problematic.…”
Section: S35mentioning
confidence: 99%